PENGARUH ECONOMICS LITERACY TERHADAP PERILAKU KONSUMSI YANG DIMEDIASI OLEH NILAI-NILAI BUDAYA LOKAL DAN PROMOSI PADA SISWA SMA NEGERI SE KOTA PAMEKASAN - Septiana, Aldila (Fakultas Ekonomi, Universitas Negeri Semarang, 2015)
This present study is aimed to investigate the influence of economics literacy on the studentsâ consumption behavior through local cultural values and promotions. The mediation used is based on the theories, the empirical studies and the previous studies.Quantitative approach is used in this study. The population is the Pamekasan Senior High Schools students (Class XI IPS, academic year 2012/2013). Proportional random sampling is conducted to take the samples in the population. The data is collected by using the questionnaire and test. Path analysis is used to analyze the data.The findings show that (1) the economic literacy level influences directly and significantly on the local cultural values, (2) the economic literacy level influences directly, negatively and significantly on the promotion, (3) the economic literacy level influences directly, negatively and significantly on the consumption behavior, (4) the local cultural values influence directly, positively and significantly on the consumption behavior, (5) the promotion influences directly, positively and significantly on the consumption behavior, (6) the economic literacy level influences indirectly and significantly on the consumption behavior through the local cultural values, and (7) the economic literacy level influences indirectly and significantly on the consumption behavior through promotion.